Total synthesis of (+)-petromyroxol, (-)-iso-petromyroxol, and possible diastereomers - Mullapudi, Venkannababu; Ahmad, Iram; Senapati, Sibadatta; Ramana, V, Chepuri (ACS Omega, 2020)
The total synthesis of (+)-petromyroxol (1) and its seven diastereomers including the ()-tso-petromyroxol (2) is described. The employed strategy involves the use of easily available CS-epimeric epoxides 5 and 5' and nonselective anomeric C1-allylation, proceeding with or without inversion at C2 thereby giving the possibility of synthesizing all possible diastereomers. Extensive two-dimensional (2D) NMR analyses of all eight diastereomers have been carried out to assign the chemical shifts of the central carbons land the corresponding attached hydrogens and to learn how the C/H-chemical shifts of the tetrahydrofuran ring were influenced by the adjacent centers.

Unified approach for the total aynthesis of Bis-THF C-15 acetogenins: a chloroenyne from laurencia majuscula, laurendecumenyne B and laurefurenynes A/B - Senapati, Sibadatta; Unmesh, Nivedya A.; Shet, Manoj N.; Ahmad, Iram; Ajikumar, Nandu; Ramana, Chepuri V. (Synthesis-Stuttgart, 2021)
A highly diastereoselective total synthesis of several bis-THF C-15 acetogenin natural products, chloroenyne from Laurencia majuscula, laurendecumenyne B, and laurefurenyries A/B, is reported. Additionally the synthesis of an advanced intermediate reported in the earlier total synthesis of (E/Z)-elatenynes (formal synthesis) is described. The salient features in the synthesis include epoxide opening, Birch reduction, Sharpless asymmetric dihydroxylation-cycloetherification, S(N)2 halogenation, and a relay cross metathesis.
Keywords: bis-THF C-15 acetogenins; carbohydrate building block; relay-cross-metathesis; S(N)2 halogenation; Sharpless asymmetric dihydroxylation-cycloetherification

Unified approach for the total synthesis of Bis-THF C-15 acetogenins: a chloroenyne from laurencia majuscula, laurendecumenyne B and laurefurenynes A/B - Senapati, Sibadatta; Unmesh, Nivedya A.; Shet, Manoj N.; Ahmad, Iram; Ajikumar, Nandu; Ramana, Chepuri V. (Synthesis-Stuttgart, 2021)
A highly diastereoselective total synthesis of several bis-THF C-15 acetogenin natural products, chloroenyne from Laurencia majuscula, laurendecumenyne B, and laurefurenyries A/B, is reported. Additionally the synthesis of an advanced intermediate reported in the earlier total synthesis of (E/Z)-elatenynes (formal synthesis) is described. The salient features in the synthesis include epoxide opening, Birch reduction, Sharpless asymmetric dihydroxylation-cycloetherification, S(N)2 halogenation, and a relay cross metathesis.
Keywords: bis-THF C-15 acetogenins; carbohydrate building block; relay-cross-metathesis; S(N)2 halogenation; Sharpless asymmetric dihydroxylation-cycloetherification